Seaweed Oligosaccharides Stimulate Plant Growth by Enhancing Carbon and Nitrogen Assimilation, Basal Metabolism, and Cell Division - Moenne-Munoz, A; Gonzalez-Figueroa, A (2013)
It is now well established that plant cell wall oligosaccharides can stimulate or inhibit growth and development in plants. In addition, it has been determined that seaweed (marine algae) cell wall polysaccharides and derived oligosaccharides can enhance growth in plants. In particular, oligo-alginates obtained by depolymerization of alginates from brown seaweeds increase growth of different plants by enhancing nitrogen assimilation and basal metabolism. Interestingly, oligo-alginates also stimulate growth of marine and fresh water green microalgae, increasing the content of fatty acids. On the other hand, oligo-carrageenans obtained by depolymerization of carrageenans from red seaweeds increase growth of tobacco plants by enhancing photosynthesis, nitrogen assimilation, basal metabolism, and cell division. In addition, oligo-carrageenans increase protection against viral, fungal, and bacterial infections in tobacco plants, which is determined, at least in part, by the accumulation of several phenylpropanoid compounds (PPCs) with antimicrobial activity. Moreover, oligo-carrageenans stimulate growth of 3-year-old Eucalyptus globulus trees by increasing photosynthesis, nitrogen assimilation, and basal metabolism. Furthermore, oligo-carrageenans induce an increase in cellulose content and in the level of essential oil and some PPCs with antimicrobial activities, suggesting that defense against pathogens may be also enhanced. Thus, seaweed oligosaccharides induce a dual beneficial effect in plants and trees, enhancing growth, which is determined by the increase in carbon and nitrogen assimilation, basal metabolism, and cell division, and defense against pathogens, which is determined by the accumulation of compounds with antimicrobial activities. In this sense, molecular mechanisms that potentially interconnect activation of plant growth and defense responses are discussed. © 2012 The Author(s).